Reorganização de classes formadas por descrições de contingências sobre escolha profissional em adolescentes - Cippola, Nathália Sabaine (2017)
Reorganizing classes of equivalent stimuli is to recombine the stimuli of the classes, forming new equivalence classes. The present work consists of three studies. Study 1 aimed at teaching the conditional relations between descriptions of contingencies about professional choice (group C) and visual stimuli (symbols of correct and incorrect [Group A] and undefined figures [Group B]), different relationships from those previously verified among participants, and check the occurrence (or not) of reorganization of classes by participants considered flexible or inflexible. Studies 2 and 3 had the goal to check if different procedures (the presentation of disparate descriptions of contingencies of those previously found in the participants’ history and a program of career guidance) could alter the stimuli classes set earlier. Forty (40) high school sophomores from ages between 15 and 16 years old participated in the study. The research was carried out in the students’ schools and the procedures were managed electronically. Study 1 was divided in six stages: survey of claims about professional choice (descriptions of contingencies), initial evaluation, pre-test, post-test, and final evaluation. All stages, except for survey of claims and initial /final evaluations, a matching-to-sample task was used. Twenty-one (21) students who did not present reorganization of classes in Study 1 participated in Study 2, and descriptions of contingencies different from descriptions previously verified among participants were presented in two ways: reading of informative material and interaction with the experimenter. After that, emerging relations were tested. In Study 3, twelve (12) participants (six inexperienced and six who went through other studies and did not reorganize classes) took part in a Career Guidance process, and then the reorganization of classes was tested. In Study 1, we could observe that 19 out of 40 participants reorganized classes, all considered flexible. In Study 2, the group who interacted with the researcher (11 students) presented a better reorganization of class compared to the other group. In Study 3, all 12 participants reorganized classes regarding the four descriptions of contingencies, and two participants considered flexible presented reorganization of all classes. In the three studies, a difference was verified about the percentage of reorganization of each class from the beginning of the procedure and easing in the evaluation of true or false statements. With these results, it was possible to observe the dependence of the degree of equivalence relationship between stimuli and conclude that maintaining the responses of agree and disagree with the assertions also depends on the pre-experimental history of the listener, such as being flexible or inflexible.